(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
In the article, when investigating the general aspect of oaths of this type, the formal-compositional structure of the oath text is given a special place, the text structure of the introductory oath, which is a part of a series of oaths, is in monological form, and the speaker perceives it orally and in writing as described, its text composition structure is three-stage. The three-stage text is monologic in micromat size and its first stage, i.e., the figurative part, is the modus of the sentence. In it, the addressee is expressed through the pronoun/me, the speaker’s full name is indicated after this pronoun, and the sentence, I swear by Almighty God, is considered a special indicator of belief, showing faith in the speaker’s speech. Expressed.